Penentuan Uji Statistik pada Penelitian Bidang Kesehatan - Reny Amalia Permata; Syaidatussalihah; Abdurahim (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
The obstacle experienced by final year students was the difficulty in carrying out research, especially when processing and analysing statistical data and presenting the right information. Especially for students majoring in health, at the research data processing stage, it is often difficult to determine the appropriate statistical test. As a result, there are many misinterpretations of research results. This community service activity aims to provide an understanding of the determination of statistical tests in health research along with case examples using SPSS software. Service activities packaged through webinar via zoom were carried out by providing material and discussions which held on May 14, 2022. The webinar was filled by two presenters, each of whom delivered material on Parametric and Non-Parametric Statistics in Health Research. The participants who took part in the activity totalled 90 participants. Before the activity started, participants were given a pre-test to find out the extent of their knowledge of statistical tests in the health sector. Then, at the end of the activity, another post-test was given. Data analysis was carried out using the t-test, to test the hypothesis whether there were differences in participants’ understanding of statistical test in the health sector before and after the webinar. Based on the results, it can be concluded that there is a significant difference between the level of understanding of the participants before and after delivering the material related to determining the appropriate statistical test in health research, indicated by the value of t-test = 24.913 is greater than t-table = 2.279 (or p-value = 0.000 is smaller than 0.05 ).